A study on kinetic and thermodynamic adsorption of fluoride from aqueous solution onto aluminium hydroxide coated rice husk ash - Tuyen, Tran Ngoc; Quyen, Nguyen Duc Vu; Hai, Ho Van Minh; Quang, Tran Ngoc; Sy, Hoang Trong; Liem, Nguyen Trong (Vietnam Journal of Science and Technology, 2016)
The fluoride adsorption on aluminum hydroxide coated rice husk ash material (RHA/Al(OH)3) was demonstrated in this study. The isothermal data indicated that the Langmuir model well described the adsorption system with the maximum monolayer adsorption capacity of 8.2 mg.g-1. The kinetic results revealed that the pseudo-second-order rate model fitted the experiments data better than the pseudo-first-order one. Furthermore, the adsorption of fluoride onto this material may be the chemical adsorption. Thermodynamic parameters (DG and DH) in the range of temperature from 30 to 70oC showed that the adsorption was a spontaneous and an endothermic process. RHA/Al(OH)3 could be used for well-treatment of fluoride contaminated well-water sampling in Ninhhoa district (Khanhhoa province). With the initial content of fluoride of 6.1 mg.L-1 and after 2 hours of treating with the dose of 4.0 ¸ 7.0 g.L-1, the concentration of fluoride in the samples decreased to 0.5 ¸ 1.5 g.L-1, that met acceptable limit of WHO.